WATER RESOURCES OF THE RUSSIAN‐KAZAKHSTAN TRANSBOUNDARY REGION AND THEIR USE - I. D. Rybkina; Zh. T. Sivokhip (Юг России: экология, развитие, 2019)
Aim. The study is aimed at examining the regional specifics of using water resources in the Russian‐Kazakhstan transboundary region, taking the current hydroclimatic situation into account.Methods. Statistical data on the availability and use of water resources in the regions of the Russian Federation and the Republic of Kazakhstan served as the initial data for the study. A comparative assessment of water supply was carried out applying traditional procedures widely used in Russia and abroad. The following indicators of water use efficiency were used: volumes of circulating and re‐sequential water supply (million m3), water losses during transportation (million m3) and water intensity of the gross regional product (GRP).Results. It was found that, over the past 20 years, a significant transformation of the water consumption structure has taken place in the studied regions. In the Russian regions, the most serious transformation of the consumption structure occurred in the agricultural sector. A comparative assessment of water supply suggests that most regions within the Russian‐Kazakhstan transboundary territory are characterized by relatively high levels of water availability.Main conclusions. The results indicate a significant impact of socio‐economic transformations in the Russian‐Kazakhstan region on the structure of water consumption, water supply, as well as indicators of water resource efficiency. The current water management problem consists in guaranteed provision of the population and economy with fresh water under the conditions of the spatio‐temporal variability of the river flow. Thus, the integrated management of water resources within the Russian‐Kazakhstan transboundary region should be based on improving the effi‐ ciency of water use in all sectors of the water economy, taking modern hydroclimatic changes into account.